How many marine aliens in Europe? - Stelios Katsanevakis; Francesca Gatto,; Argyro Zenetos; Ana Cristina Cardoso (Management of Biological Invasions, 2013)
In the framework of the European Alien Species Information Network (EASIN; http://easin.jrc.ec.europa.eu/), an inventory of marine alienspecies in Europe was created by critically reviewing existing information in 34 global, European, regional and national databases. In total, 1369 marine alien species have been reported in the European seas (including 110 cryptogenic and 139 questionable species); this is a substantial increase from the 737 species previously reported in 2009 based on the DAISIE (Delivering Alien Invasive Species Inventories for Europe; http://www.europe-aliens.org) dataset. Most of the reported species were invertebrates (63.3%), followed by chromists (13.7%), vertebrates (11.6%), and plants (10.1%). Mollusca is the most numerous phylum, followed by Arthropoda, Chordata, and Annelida. Thecountries with the highest reported numbers of marine alien species were Israel, Turkey, Italy, France, Egypt and Greece. A reporting bias is evident as efforts for monitoring and reporting alien species vary among countries.